Description of zoeal stages of Albunea paretii Guérin-Méneville, 1853 (Decapoda: Albuneidae) collected from the Amazon Continental Shelf (Brazil) - Rodrigues, Ana Carolina Melo; Santos, Antonina Dos; Martinelli-Lemos, Jussara Moretto (Zootaxa, 2020)
The present work describes and illustrates in detail the six zoeal stages of Albunea paretii collected from plankton samples on the Amazon continental shelf in Brazil. The morphological characters are compared with those of other known albuneid larvae. As in other albuneids, the zoeae of Albunea paretii have a semi-globose carapace, a long rostral spine and a pair of long posterolateral spines on pereon, as well as three aesthetascs on the antennule of zoea I, a strong antennal spinous process and a convex telson with a stout posterolateral spine. The zoeal morphology of Albunea paretii and other species of the genus differs, especially regarding the unique presence of the posterolateral spine only on the 5th pleonite in zoea I–IV and the absence in later zoeal stages. The differing features of the albuneid subfamilies are in the telson, antenna and maxilla format and number of setae.